Textbook of Hyperbaric Medicine - Jain, Kewal K.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This comprehensive volume captures the latest scientific evidence, technological advances, treatments and impact of biotechnology in hyperbaric oxygen therapy. Divided into three distinct sections, the book begins with basic aspects that include history, equipment, safety and diagnostic approaches; this is followed by clinical applications for hyperbaric oxygen therapy in various modalities; the last section provides an overview of hyperbaric medicine as a specialty with best practices from around the world. Integration of multidisciplinary approaches to complex disorders are also covered. Updated and significantly expanded from previous editions, Textbook of Hyperbaric Medicine, 6th Edition will continue to be the definitive guide to this burgeoning field for students, trainees, physicians and specialists. .
Part I. Basic Aspects -- Chapter 1. The History of Hyperbaric Medicine -- Chapter 2. Physical, Physiological, and Biochemical Aspects of Hyperbaric Oxygenation -- Chapter 3. Effects of Diving and High Pressure on the Human Body -- Chapter 4. Physical Exercise under Hyperbaric Conditions -- Chapter 5. Hypoxia -- Chapter 6. Oxygen Toxicity -- Chapter 7. Hyperbaric Chambers: Equipment, Technique, and Safety -- Chapter 8. Indications, Contraindications, and Complications of HBO Therapy -- Chapter 9. Drug Interactions with Hyperbaric Oxygenation -- Chapter 10. Neurophysiologic SPECT Brain Function Imaging and Hyperbaric Oxygen Therapy -- Part II. Clinical Applications -- Chapter 11. Decompression Sickness -- Chapter 12. Cerebral Air Embolism -- Chapter 13. Carbon Monoxide and Other Tissue Poisons -- Chapter 14. HBO Therapy in Infections -- Chapter 15. Hyperbaric Oxygen Therapy and Chronic Lyme Disease: The Controversy and the Evidence -- Chapter 16. HBO Therapy in Wound Healing, Plastic Surgery, and Dermatology -- Chapter 17. HBO Therapy in the Management of Radionecrosis -- Chapter 18. The Use of HBO in Treating Neurological Disorders -- Chapter 19. Role of Hyperbaric Oxygenation in the Management of Stroke -- Chapter 20. HBO Therapy in Global Cerebral Ischemia/Anoxia and Coma -- Chapter 21. HBO Therapy in Neurosurgery -- Chapter 22. Oxygen Treatment for Multiple Sclerosis Patients -- Chapter 23. HBO in the Management of Cerebral Palsy -- Chapter 24. HBO Therapy in Miscellaneous Neurological Disorders -- Chapter 25. HBO Therapy in Cardiovascular Diseases -- Chapter 26. HBO Therapy in Hematology and Immunology -- Chapter 27. HBO Therapy in Gastroenterology -- Chapter 28. HBO and Endocrinology -- Chapter 29. HBO and Pulmonary Disorders -- Chapter 30. Hyperbaric Oxygenation in Traumatology and Orthopedics -- Chapter 31. HBO Therapy in Otolaryngology -- Chapter 32. HBO Therapy and Ophthalmology -- Chapter 33.Hyperbaric Oxygenation in Obstetrics and Gynecology -- Chapter 34. Use of Hyperbaric Oxygenation (HBO2) in Neonatal Patients -- Chapter 35. Hyperbaric Oxygenation in Geriatrics -- Chapter 36. HBO as an Adjuvant in Rehabilitation and Sports Medicine -- Chapter 37. Nursing and Hyperbaric Medicine -- Chapter 38. Role of HBO in Enhancing Cancer Radiosensitivity -- Chapter 39. HBO Therapy and Organ Transplants -- Chapter 40. Hyperbaric Oxygen Pretreatment and Preconditioning -- Chapter 41. Anesthesia in the Hyperbaric Environment -- Chapter 42. Hyperbaric Oxygen in Resuscitation -- Chapter 43. HBO in Military Medicine -- Part III. Hyperbaric Medicine as a Specialty -- Chapter 44. Training and Practice of Hyperbaric Medicine -- Chapter 45. Research in Hyperbaric Medicine -- Chapter 46. Personalized Hyperbaric Medicine -- Chapter 47. The Future of Hyperbaric Medicine -- Chapter 48. Ethical Issues, Standards, and Quality Control in the Practice of Hyperbaric Medicine -- Chapter 49. Hyperbaric Medicine in Europe -- Chapter 50. Hyperbaric Medicine in the United States -- Chapter 51. Hyperbaric Medicine in Latin America.
Keywords: Medicine; Internal medicine; Medical biochemistry; Rehabilitation; Medicine & Public Health; Internal medicine; Medical biochemistry; Rehabilitation